La gingivitis en los escolares de la escuela “Lucas Tanguila” comunidad Quichua de alto Huino, parroquia puerto Murialdo, cantón Loreto durante el periodo de septiembre del 2013 a febrero del 2014 - Marco Alfredo, Fierro Ríos (2014)
The titled investigation topic: The gingivitis in the scholars of the School "Lucas Tanguila", community Quichua of High Huino, parish Murialdo, canton Loreto during the period of September of the 2013 to February of the 2014, takes as starting point the concepión that the gingivitis constitutes one of the commonly identified periodontal alterations in school and it can cause severe alterations, affecting the integrity of the system estomatognático. Objectives. The objective is to determine the gingivitis prevalencia like premise of the buccal health in the scholars of the School "Lucas Tanguila", community Quichua of High Huino, parish Port Murialdo, canton Loreto during the period of September of the 2013 to February of the 2014. He/she is carried out the taking of primary data to elaborate the capítuloI that is the theoretical Marco where is approached the main theories and conceptualizations of the gingivitos and the oral education. Methodology. They were studied 24 scholars with an age range between 6 and 11 years, using the index gingival of Löe-Silness, with the help of a periodontal probe. He/she was carried out a support questionnaire and the interpretation of the obtained results was carried out by means of the use of the program Microsoft office Excel Results. The gingivitis prevalencia was of 98%. The inflammation grade that I prevail was moderate. Summations. The gingivitis is a buccal pathology that in the scholars for lack of a good buccal health prevails, in and of itself it is recommended to implement campaigns of education managed odontológica to these groups of risk to foment a good habit of buccal hygiene. Finally it is elaborated a training proposal and orientation as regards buccal health directed to school.